Forty-five years of One Health-related research at the International Livestock Research Institute - Grace, Delia; McIntire, John (International Livestock Research Institute, 2022)
Objective: Livestock are the engine of development, but disease is a major constraint to production and risk to human health. Epidemiological research has revolutionised management of livestock disease, and this poster reviews 45 years research by the International Livestock Research Institute (ILRI), the only international agricultural research institute focused on livestock. Materials and Methods: Over four years, we engaged more than 70 expert authors, to document 45 years of livestock research at ILRI, resulting in a book, launched in 2021 (Figure 1). Nine of the 18 chapters document epidemiological research into animal disease, showing the importance of epidemiology in livestock development. Results: Key findings include: • Research increased understanding of infection dynamics and generated methodologies and approaches that have since been applied in every corner of the world. • One Health approaches estimated the burden and risk factors for neglected as well as emerging zoonoses, identified their drivers and developed strategies for reducing those risks. • Field research on trypanosomiasis determined that rational use of curative and preventive trypanocidal drugs is the most sustainable and scalable control method. • Research on food safety elevated the importance of informal markets where most of the poor buy and sell food, introduced risk assessment developing countries, conducted dozens of disease burden studies and developed new approaches to managing food safety in informal markets. Conclusion: The book captures ILRI benefits to research, capacity development and end users. It marshals substantial evidence to show that livestock epidemiological and economic research improved food and nutrition security, prosperity, and natural resource management in lower-income countries.